PENGARUH PERSEPSI HARGA, BRAND IMAGE, DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PERSPIREX DEODORANT DI SHOPEE PADA MAHASISWA FEB UNTAG SURABAYA - Berlian Ardani Suaidy; Yulyar Kartika Wijayanti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Purchase decision refers to the process in which consumers decide to buy a product or service based on various considerations. Understanding the characteristics of personal care products such as deodorants and the factors that influence consumer decisions is an important step in enhancing a brand’s competitiveness. One notable personal care product that draws research interest is Perspirex Deodorant, which is actively marketed through e-commerce platforms such as Shopee. Three main factors are assumed to influence purchase decisions in this study: Price Perception, Brand Image, and Social Media Marketing. Competitive pricing can enhance consumer appeal, a strong brand image can strengthen consumer trust in a product, and targeted social media marketing an shape perception and buying interest. This study aims to determine the effect of Price Perception, Brand Image, and Social Media Marketing on the Purchase Decision of Perspirex Deodorant among FEB Untag Surabaya students. The research uses a quantitative approach with data collected through questionnaires distributed to 100 respondents. The results indicate that all three variables have a positive and significant influence on Purchase Decision. Therefore, these factors are important considerations in marketing strategies for deodorant products on digital platforms.